2017
DOI: 10.1177/0256090916686681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Online Shopping Values and Website Cues on Purchase Behaviour: A Study Using S–O–R Framework

Abstract: The e-commerce industry in India has seen unprecedented growth in last few years. Eyeing India's substantial e-retail opportunity across multiple segments, investors have been aggressively funding the e-commerce sector. This growth has been fuelled by rapid adoption of technology, improving standards of living, an increasing young population, and economically advancing middle class, besides increasing access to the Internet through broadband and use of smartphones and tablets. The entry of global e-commerce gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 70 publications
9
55
0
5
Order By: Relevance
“…Based on that the researcher is expecting that good atmospheric cues in website will make the consumers more satisfied about the services provide by the website. as this hypothesis is compatible with other studies hypothesis such as: (Abrar, Zaman, & Satti, 2017;Prashar, Sai Vijay, & Parsad, 2017;Sai Vijay et al, 2019;Sreejesh & Abhilash, 2017).…”
Section: Proposed Model and Relationssupporting
confidence: 93%
“…Based on that the researcher is expecting that good atmospheric cues in website will make the consumers more satisfied about the services provide by the website. as this hypothesis is compatible with other studies hypothesis such as: (Abrar, Zaman, & Satti, 2017;Prashar, Sai Vijay, & Parsad, 2017;Sai Vijay et al, 2019;Sreejesh & Abhilash, 2017).…”
Section: Proposed Model and Relationssupporting
confidence: 93%
“…It also arises from misplacing information from the sellers [34], additional charges [35], pop-ups [36], or bad experience with website design [37]. Xia and Sudharshan [38] confirmed that the right configuration of pop-up might increase the online sales, but wrong setup might lead to the detrimental.…”
Section: E Technical Problemmentioning
confidence: 99%
“…Customer-based strategy is developed on the basis of consumer information. The strategy is developed based on deep understanding of consumers' insight of their wants and needs [32]; [33], the costs incurred by consumers to buy and own goods and services [34], the convenience of obtaining goods and services [35]; [36], or what makes communication between organizations and consumers more effective [6]. All of this information shares a focus on consumers as the unit of analysis: data on needs, purchase and ownership costs, convenience and efficiency of communication can be collected for each consumer.…”
Section: B Costumer-based Strategymentioning
confidence: 99%